2021
DOI: 10.1038/s41598-021-03819-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cymbopogon flexuosus (Poaceae) essential oil and primary components on the eclosion and larval development of Aedes aegypti

Abstract: The current study describes the effects of sub-lethal concentrations and constituent compounds (citral and geranyl acetate) of Cymbopogon flexuosus essential oil (EO) on the development of Aedes aegypti. We treated eggs with 6, 18, or 30 mg L−1 and larvae with 3 or 6 mg L−1 of EO and its major compounds (citral and geranyl acetate). Citral and geranyl acetate were evaluated at 18, 30, and 42 mg L−1 and compared with commercial growth inhibitors (diflubenzuron and methoprene). We measured larval head diameter, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Trans-cinnamaldehyde showed a toxic effect against the eggs of P. humanus capitis 37 , and Spodoptera littoralis 19 . Finally, Castillo-Morales et al 38 reported that geranial provided strong ovicidal activity against Ae. aegypti.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trans-cinnamaldehyde showed a toxic effect against the eggs of P. humanus capitis 37 , and Spodoptera littoralis 19 . Finally, Castillo-Morales et al 38 reported that geranial provided strong ovicidal activity against Ae. aegypti.…”
Section: Discussionmentioning
confidence: 99%
“…Geranial inhibits the acetylcholinesterase (AChE) enzymes of neural cells and neuroreceptors 30 . Castillo-Morales et al 38 concluded that geranial penetrates through the serosal cuticle of an embryo and disturbs the embryogenesis process. Hence, the synergistic effect of the combination may stem from the fact that both substances acted along two different pathways, reinforcing one another.…”
Section: Discussionmentioning
confidence: 99%
“…Trans-cinnamaldehyde showed a toxic effect against the eggs of P. humanus capitis 34 , and Spodoptera littoralis 18 . Finally, Castillo-Morales et al 35 reported that geranial provided strong ovicidal activity against Ae. aegypti.…”
Section: Discussionmentioning
confidence: 99%
“…Geranial inhibits the acetylcholinesterase (AChE) enzymes of neural cells and neuroreceptors 40 . Another author, Castillo-Morales et al 35 concluded that geranial penetrates through the serosal cuticle of an embryo and disturbs the embryogenesis process. Hence, the synergistic effect of the combination may stem from the fact that both substances acted along two different pathways, reinforcing one another.…”
Section: Discussionmentioning
confidence: 99%
“…Allium sativum (garlic) and Cymbopogon citratus (lemon grass) are plants commonly known and used for their medicinal values in many countries of the world including Nigeria (Odugbemi and Akinsulire, 2006). Previous studies on their phytochemical extracts at different concentrations have shown some insecticidal activities against larvae of mosquito vector species (Ebe et al, 2015;Muhammad et al, 2019;Sitorus et al, 2020;Aminu et al, 2021;Castillo-Morales et al, 2021;). Synergistic combinations of two or more compounds can reduce the adverse effects brought on by high dosages of a single agent, access context-specific multitarget mechanisms, and reduce the chance of resistance development (Lehar et al, 2009;Youssefi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%